Timing of therapeutic interventions against infection-triggered encephalopathy syndrome: a scoping review of the pediatric literature - Nagase, Hiroaki; Yamaguchi, Hiroshi; Tokumoto, Shoichi; Ishida, Yusuke; Tomioka, Kazumi; Nishiyama, Masahiro; Nozu, Kandai; Maruyama, Azusa (Frontiers in Neuroscience, 2023)
Our goal was to conduct a scoping review of the literature on the treatment of infection-triggered encephalopathy syndrome/acute encephalopathy in children, focusing on treatment targets and treatment initiation timing. We performed literature searches using PubMed for articles reporting treatments of infection-triggered encephalopathy syndrome/acute encephalopathy. We included articles describing specific treatments for acute encephalopathy with control groups. For the purpose of searching new therapies only experimentally tried in the case series, we also included case series studies without control groups in this review, if the studies contained at least two cases with clear treatment goals. Therapies were classified based on their mechanisms of action into brain protection therapy, immunotherapy, and other therapies. We operationally categorized the timing of treatment initiation as T1 (6-12 h), T2 (12-24 h), T3 (24-48 h), and T4 (>48 h) after the onset of seizures This is a provisional file, not the final typeset article and/or impaired consciousness. Thirty articles were included in this review; no randomized control study was found. Eleven retrospective/historical cohort studies and five case-control studies included control groups with or without specific therapies or outcomes. The targeted conditions and treatment timing varied widely across studies. However, the following three points were suggested to be effective in multiple studies: 1) Careful seizure management and targeted temperature management within 12 h (T1) of onset of febrile seizure/prolonged impaired consciousness without multiple organ failure may reduce the development of acute encephalopathy with biphasic seizures and late reduced diffusion; 2) immunotherapy using corticosteroids, tocilizumab, or plasma exchange within 24 h (T1-T2) of onset of acute necrotizing encephalopathy may reduce sequelae; and 3) anakinra therapy and ketogenic diet demonstrate little evidence of neurologic sequelae reduction, but may reduce seizure frequency and allow for weaning from barbiturates, even when administered weeks (T4) after onset in children with febrile infection-related epilepsy syndrome. Although available studies have no solid evidence in the treatment of infection-triggered encephalopathy syndrome/acute encephalopathy, this scoping review lays the groundwork for future prospective clinical trials.